(untitled) (MIST International Journal of Science and Technology, 2025)
This study investigates the diurnal, seasonal, and latitudinal variations of Spread F and the Rate of TEC Index (ROTI) over North America during the high solar activity period of 2014. Using GNSS-based ROTI measurements and Digisonde ionograms from multiple stations, we systematically analyze the relationship between Spread F occurrences and ROTI enhancements. The analysis incorporated Diurnal and seasonal variations to determine dominant trends and potential driving mechanisms, such as medium-scale traveling ionospheric disturbances (MSTIDs) and polarization electric fields. Seasonal and latitudinal variations of Spread F occurrences and ROTI fluctuations are found to be strongly linked to MSTIDs and geomagnetic activity. A clear seasonal dependence was observed at the stations situated under the transitional and mid-latitude regions of the ionosphere. The maximum irregularity occurred in April for transitional region stations and in November for mid-latitudinal stations. Additionally, Spread F and ROTI exhibit similar diurnal and seasonal trends, with maximum irregularity occurrences during nighttime (20:00–02:00 LT). A distinct seasonal dependence is observed, with transitional region stations peaking in winter and mid-latitude stations in summer. Notably, spread F was consistently associated with notable ROTI values (>0.15 TECU/min), suggesting gravity waves and polarization electric fields as driving mechanisms. Through detailed case studies, we demonstrated that MSTIDs, likely driven by gravity wave dynamics, play a crucial role in generating plasma irregularities, which in turn enhance ROTI values and contribute to Spread F formation. Under quiet geomagnetic conditions, these irregularities exhibit a strong daytime preference. Conversely, during disturbed geomagnetic conditions (e.g., the geomagnetic storm), the spatial extent of ionospheric irregularities increased significantly, affecting both transitional and mid-latitude stations for both daytime and nighttime. By demonstrating a persistent relationship between Spread F and ROTI, this study advances ionospheric modelling efforts and supports the development of improved space weather forecasting techniques, crucial for GNSS-based navigation and communication systems. MIJST, Vol. 13, June 2025 : 09-27 DOI: https://doi.org/10.47981/j.mijst.13(01)2025.529(09-27)